2014
DOI: 10.1002/cta.2013
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependant crosstalk analysis in coupled single‐walled carbon nanotube (SWCNT) bundle interconnects

Abstract: The temperature‐dependent, crosstalk‐induced, noise voltage waveform and its frequency spectrum, in capacitive coupled single‐walled carbon nanotube (SWCNT) bundle interconnects, at the far end of victim line, have been analyzed at 22‐nm technology node. A similar analysis is performed for copper interconnects and a comparison is made between the results of these two analyses. The SPICE simulation results reveal that at temperature variations ranging from 300 to 500 K, compared with conventional metal (copper)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…For all calculation and simulation purposes, the data shown in Table 1 have been used. 20,21,38,39 The result also illustrates that coupled copper interconnects have comparatively lower crosstalk-induced positive noise voltage peaks because of the control of its smaller self-inductance (L s ) and a larger ground capacitance (C g ) compared with MLGNR. These results show the significant reflection of temperature variation on interconnect resistance (see Figures 4 and 5).…”
Section: Crosstalk Analysismentioning
confidence: 83%
See 4 more Smart Citations
“…For all calculation and simulation purposes, the data shown in Table 1 have been used. 20,21,38,39 The result also illustrates that coupled copper interconnects have comparatively lower crosstalk-induced positive noise voltage peaks because of the control of its smaller self-inductance (L s ) and a larger ground capacitance (C g ) compared with MLGNR. These results show the significant reflection of temperature variation on interconnect resistance (see Figures 4 and 5).…”
Section: Crosstalk Analysismentioning
confidence: 83%
“…20,34,35,38,39 It is also reported that, 20,21 with advancement of technologies, the resistance of interconnect increases because of strong alteration of temperature-dependent scattering on the MFP. 20,34,35,38,39 It is also reported that, 20,21 with advancement of technologies, the resistance of interconnect increases because of strong alteration of temperature-dependent scattering on the MFP.…”
Section: Crosstalk Analysismentioning
confidence: 98%
See 3 more Smart Citations